The OECD's BEPS Project and the Myth of the End of International Fiscal Planning: A Critical Approach on the subject of the Final Reports 2015 - Ramos Angeles, Jesús Alberto (2015)
This article evaluates and proposes a critique on the OECD’s BEPS Project. In the first three sections of the article behavioral logic of multinational companies are exposed, as well as the economic context in which the BEPS initiative arises and harmful tax practices develop. In subsequent sections we approach the objectives and principles of the BEPS plan and also addressed a critique of its development. Finally, we conclude that the BEPS plan has both structural and functional defects, although they are the best contemporary effort to counter BEPS, it is insufficient to curb multinationals aggressive tax planning practices.